MicroRNA expression profiles of cancer stem cells in head and neck squamous cell carcinoma - YATA, KAZUYA (Int J Oncol, 2015)
Increasing evidence indicates that cancer stem cells have essential roles in tumor initiation, progression, metastasis and resistance to chemo-radiation. Recent research has pointed out biological importance of microRNAs in cancer stem cell dysregulation. Total number of mature microRNAs in human genome increased to more than 2,500 with the recent up-date of the database. However, currently no information is available regarding microRNA expression profiles of cancer stem cells in head and neck squamous cell carcinoma (HNSCC). Increased ALDH1 activity has been demonstrated as a reliable marker for isolation of cancer stem cells. Therefore, we evaluated the microRNA expression profile of ALDH1-high subpopulations in the HNSCC cell lines UTSCC-9 and UTSCC-90. Initially, we examined cancer stem cell properties of ALDH1-high subpopulations in both cell lines. We analyzed expression of stemness markers, sphere formation capacity and xenograft transplantation into NOD/SCID mice. Our findings validated that ALDH1-high subpopulations showed significantly increased tumor-initiating ability. Furthermore, we investigated the microRNA expression profile of HNSCC stem cells using microRNA array and confirmed the results by quantitative real-time PCR. We found that expressions of miR-424, let-7a, miR-6836, miR-6873 and miR-7152 were downregulated, whereas miR-147b was upregulated with statistical significance in the ALDH1-high subpopulation. In conclusion, we identified a subset of microRNAs that were differentially expressed in ALDH1-high subpopulation, providing new microRNA targets to study dysregulation of HNSCC-initiating cells and develop therapeutic strategies aimed at eradicating the tumorigenic stem cells in HNSCC.